Foraging activity of Polybia occidentalis venezuelana (Hymenoptera, Vespidae) - HERNÁNDEZ-D., JOHN; SARMIENTO, CARLOS E.; FERNÁNDEZ H., CLAUDIO (Revista Colombiana de Entomología, 2009)
In order to characterize some aspects of foraging in Polybia occidentalis venezuelana in the region of Monteria (Cordoba), observations were made over 20 hours at six nests located in three zones of vegetation. The number of wasps departing and returning to the nest was recorded from 07:00 to 18:00 hours and the solid food brought to the nest was identified. The range of foraging was estimated. High temperatures and low relative humidities positively influenced the departure frequency of foragers from the nest. Foraging for liquid constituted 53% of the events, while foraging for food was 18.5% and pulp for nest construction was 12.8%. Prey items consisted of Lepidoptera (58.5%), Diptera (20.5%), Hemiptera (6.7%), Coleoptera (2.7%), and Hymenoptera (2.1%). Spodoptera frugiperda was the more frequent species; the remaining 9.2% constituted unidentified material. The flight range of P. occidentalis venezuelana was about 50 m, resulting in a main foraging area of 7,854 m 2. On average a colony captured 72 prey per day and an adult lifted up to 39% of its own weight on each trip. The diet described for this species, as well as the foraging range, coincide with studies conducted in other regions and highlight the potential of Polybia occidentalis venezuelana for biological control programs in agroecosystems of the Cordoba department.